Povezanost glasbenih preferenc z depresivnostjo pri mladostnikih - Burian, Urška; Malešič, Diana; Bankovič, Anja; Habe, Katarina (Revija za elementarno izobraževanje, 2019)
The relation between musical preferences and depression among adolescents. Adolescents are a population that is particularly vulnerable to the effects of music, while depression is the most common  psychopathology in this developmental period. Studying the connection between musical preferences and depression in adolescents therefore needs to be given special attention. The purpose of our study was to  examine how different musical preferences are associated with depression and whether these links differ according to gender. The database collected on a sample of 272 adolescents (193 female and 79 male) was obtained using the Beck Depression Inventory - BDI II and the Short Test of Music Preferences - STOMP. On the basis of results from the research, we found that a preference for Reflective & Conventional music styles was connected negatively to depression, while a preference for the Rebellious music style is positively connected to depression. The important value of our research consists in our having tested the Slovene  version of STOMP. The results show that STOMP’s validity is questionable.DOI: 10.18690/rei.12.1.113-138.2019 COBISS-ID: 24678408
Keywords: depression; musical preferences; adolescence; functions of music; effects of music